2021
DOI: 10.1371/journal.pone.0254222
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine interventions for hypertension management in low- and middle-income countries: A scoping review

Abstract: Hypertension remains the leading cause of cardiovascular disease worldwide and disproportionately impacts patients living in low- and middle-income countries (LMICs). Telemedicine offers a potential solution for improving access to health care for vulnerable patients in LMICs. Objectives The purpose of this scoping review was to summarize the evidence for telemedicine interventions for blood pressure management in LMICs and assess the relationships between the telemedicine intervention characteristics and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
(124 reference statements)
2
20
0
Order By: Relevance
“…Prior research includes, for example, a scoping review conducted by Hoffer-Hawlik et al ( 8 ), who investigated telemedicine interventions for blood pressure control in LMICs and found that blood pressure was significantly reduced in telemedicine interventions, although the magnitude of the impact was not always substantial. They concluded that telemedicine may be an effective technique for boosting access to care and enhancing outcomes for hypertension in LMICs, especially during events that limit access to in-person care, such as the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research includes, for example, a scoping review conducted by Hoffer-Hawlik et al ( 8 ), who investigated telemedicine interventions for blood pressure control in LMICs and found that blood pressure was significantly reduced in telemedicine interventions, although the magnitude of the impact was not always substantial. They concluded that telemedicine may be an effective technique for boosting access to care and enhancing outcomes for hypertension in LMICs, especially during events that limit access to in-person care, such as the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the challenges they and the telemedicine literature highlight hold relevance to our findings broadly. These have to do with technological barriers, digital literacy, financial and security aspects 17 42 48–52. We found an inequitable regional distribution in DHI implementation with most implementations in the Americas, especially the USA.…”
Section: Discussionmentioning
confidence: 86%
“…Digital technologies are increasingly being recognised as critical innovations to strengthen health services delivery systems 54–56. Thus, it becomes imperative to address the above aspects for scalability and continued uptake, considering the widespread use and integration of telemedicine in routine NCD care 49. COVID-19 restrictions made digital solutions necessary in many social sectors, and this society-wide transition is poised to significantly change the ways in which whole societies engage in, and enact health 57.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, increased physical activity levels were advised and monitored by simply using a pedometer or an accelerometer. Aerobic exercise was shown as an effective treatment for blood pressure improvement in hypertensive patients [13,41,42] Evidence suggests that the aerobic exercise performed at 65-75% heart rate reserve, 90-150 min/week [6], shows overall reductions in SBP of −4.1 mmHg and DBP of −2.2 mmHg; the blood pressure lowering effects of dynamic resistance (90-150 min per week, 50-80% one repetition maximum, six exercises, three sets per exercise, ten repetitions per set) were −3.7 mmHg and −2.7 mmHg for systolic and diastolic blood pressure, respectively [39]. When combined, the overall effects of aerobic training and resistance exercise are reductions of −5.5 mmHg and −4.1 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ruberti et al [44], safety assessment in a home-based exercise intervention is crucial, and a careful evaluation of the electronic medical record, multidisciplinary consultations, and self-monitoring are important strategies to guarantee the intervention security and effectiveness. Still, no reference to exercise professionals is apparent in several reviews focusing on telemedicine interventions in hypertension management [13,45,46]. A comprehensive study including cardiorespiratory fitness, physical fitness levels, muscle function, traditional cardiovascular risk factors, and health-related quality of life, compared the long-term effects of a 12-week home-based physical training intervention with telemonitoring guidance to a prolonged 12-week center-based cardiac rehabilitation intervention, showing no differences between the two program settings in exercise capacity and physical activity levels [32].…”
Section: Discussionmentioning
confidence: 99%